Climate Trends in Coari/AM-Brazil - Aleixo, Natacha Cintia Regina [UNESP]; Filho, Luciomar da Silva Almeida (Revista Brasileira de Geografia Fisica, 2022)
The objective of this work was to analyze the trends of rainfall and air temperature of the municipality of Coari, Amazonas, Brazil, considering the historical series from 1970 to 2015. The data were obtained from the INMET website in monthly and annual time scale and correspond to the conventional station data, after filling gaps the non-parametric Mann-Kendall and Pettitt tests were applied to verify the trend and homogeneity, respectively. The results showed that the significance was greater than 0.05 for rainfall representing the absence of a significant trend in annual and monthly data, whereas for air temperature there was a significant positive trend in maximum temperature, with a continuous increase from the year 2000 and minimum temperature from 1997, for annual and monthly data. In general, it was possible to attest to the effectiveness of statistical methods in the consolidation of responses for analysis of climate change, and it is possible to affirm that there were positive trends of increasing air temperature recorded in Coari and stationarity of rainfall data.
Tendências climáticas em Coari-AM
Keywords: Climate Change; Geographical climatology; Non-parametric tests